ANALISIS KESESUAIAN PRODUK TABUNGAN HAJI DENGAN AKAD WADIAH BERDASARKAN STANDAR AKUNTANSI KEUANGAN (SAK) SYARIAH 2020 STUDI KASUS PADA PT BANK ACEH SYARIAH - Nur Afni Yunita; Muhammad Yusra Yusra; Arliansyah Arliansyah; Utari Orijayanti (el-Amwal, 2022)
This study aims to determine the suitability of Hajj savings products with wadiah contracts based on Sharia Financial Accounting Standards (SAK) applied to PT Bank Aceh Syariah whether they are in accordance with the accounting treatment in them. This research is a type of descriptive qualitative research, data collection techniques by means of interviews, observations, literature studies. The results of this study indicate that PT Bank Aceh Syariah has implemented a wadiah contract in accordance with Sharia Financial Accounting Standards (SAK) for Hajj savings products.